Dynamics of adsorbed polymers on attractive homogeneous surfaces - Yang, Qing-Hui (Sci Rep, 2016)
Dynamic behaviors of polymer chains adsorbed on an attractive, homogeneous surface are studied by using dynamic Monte Carlo simulations. The translational diffusion coefficient D(xy) parallel to the surface decreases as the intra-polymer attraction strength E(PP) or the polymer-surface attraction strength E(PS) increases. The rotational relaxation time τ(R) increases with E(PS), but the dependence of τ(R) on E(PP) is dependent on the adsorption state of the polymer. We find that τ(R) decreases with increasing E(PP) for a partially adsorbed polymer but it increases with E(PP) for a fully adsorbed polymer. Scaling relations D(xy) ~ N(−α) and τ(R) ~ N(β) are found for long polymers. The scaling exponent α is independent of E(PS) for long polymers but increases with E(PP) from α = 1.06 at E(PP) = 0. While β ≈ 2.7 is also roughly independent of E(PS) for the adsorbed polymer at E(PP) = 0, but β increases with E(PS) at E(PP) > 0. Moreover, we find that β always decreases with increasing E(PP). Our results reveal different effects of the attractive surface on the diffusion and rotation of adsorbed polymers.